Reflexões sobre o desenvolvimento do nordeste: o Pensamento Cepalino e a Teoria da Dependência - BURNETT, Annahid (Universidade Federal do Pará, 2021)
Two theories, one that emerged from the other, bring slightly different readings about the reproduction of the capitalist production system on the development of countries. This article discusses the approach of CEPAL and the Theoryof Dependence to argue about the process of implementation of the capitalist model of production in the Northeast and how to think regional development models, such as the Northeast Development Superintendence. We used as methodology the review of the literature relevant to the approaches of CEPAL, the Theory of Dependence, as well as the theories of globalization and Brazilian social thought. We observed that the development model adopted by Sudene did not incorporate structural changes, resulting in increased land concentration and social inequalities.